(untitled) (Per Musi, 2023)
The movement Claviers was composed for percussion keyboards and is part of Pléïades (1978) for six percussionists. Based on evidence from different archives, direct correlations with elements of traditional Indonesian music are highlighted here. The evidence points to the insertion of materials with which Xenakis had contact in the 1950s and during his trip to Bali and Java in 1972-1973. The insertion of exogenous material is rare within his work, but in Claviers it is a substantial part of the creative process, bringing a particular meaning to the structural treatment and sequence of sections that characterizes the movement. In doing so, the composer creates an underlying discourse and a rather dynamic context within this movement, and it points to correlations not yet examined in a broader part of his work. This dynamic context has very profound implications with Xenakis’ compositional thought and practice, bringing new elements to understanding part of the creative process during a very prolific phase of his life.